Testimonios: la comprensión y la culpa - Ilaria Magnani (Confluenze, 2013)
After 35 years from Argentina's last military coup, memory, according to Assmann, is shifting from individual to cultural. In literature this means to continue "speaking the unspeakable" (Reati), which, from WW 2 onward, is a key-point of literary production associated to repression. In this paper we analyze some recent works from a cultural (Sarlo, Vezzetti) and imaginary (Durand, Bachelard) perspective aiming to demonstrate the existence of a new category of testimonies.